Melampaui Keterampilan Teknis: Analisis Kesenjangan Antara Harapan Petani dan Realitas Kinerja Penyuluhan Pertanian - Rizki Nandi; Hendry Kurniawan; Heffi Christya Rahayu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to analyze the level of rice farmer satisfaction with the performance of agricultural extension services in Pasir Baru Village, Rokan Hulu Regency. This research specifically aimed to identify the priority attributes of the extension service that require improvement and to measure the overall satisfaction level of the farmers. Materials and methods. This research employed a descriptive quantitative approach. The study involved a census of 45 rice farmers in Pasir Baru Village. Data were collected through questionnaires measuring the perceived importance and performance levels of 21 service attributes. The collected data were then analyzed using the Customer Satisfaction Index (CSI) to determine the overall satisfaction level and Importance-Performance Analysis (IPA) to identify strategic priorities for service improvement. Results. The analysis revealed that the overall farmer satisfaction index (CSI) was 74.504%, classifying the farmers' satisfaction level as